Organization climate and job satisfaction: a rigorous quantitative analysis of their relationship (2015)
This paper analyzes the relationship between organization climate and job satisfaction in organizations that provide health services, particularly in a hospital. A rigorous quantitative methodology is used, through the application of principal component analysis and confirmatory factor analysis of constructs, in order to test the measurement model of the instrument employed. Additionally, through structural equations the relationship between the aforementioned constructs is analyzed. The main goal is to enhance the validity of the descriptive results yielded by similar studies in other countries, as well as to propose a model generally applicable to other types of organizations as a basis for implementing strategies aimed at better management of human talent. The results of this study corroborate and enrich, through an innovative and easy-to-apply measurement tool, conclusions of previous studies regarding the direct relationship between these constructs. Furthermore, the conclusions drawn can be used to design strategies enabling a more efficient management of existing human talent in such organizations.